Bethe lattice approach study of the mixed spin-1/2 and spin-7/2 Ising model in a longitudinal magnetic field - Eddahri, S.; Karimou, M.; Razouk, A.; Hontinfinde, F.; Benyoussef, A. (Condensed Matter Physics, 2018)
The magnetic properties of the mixed spin- 1/2 and spin- 7/2 Ising model with a crystal-field in a longitudinal magnetic field are investigated on the Bethe lattice using exact recursion relations. The ground-state phase diagram is constructed. The temperature-dependent one is displayed in the case of uniform crystal-field on the (kBT/|J|, D/|J|) plane in the absence of the external constraint for lattice coordination numbers z = 3, 4, 6. The order parameters and corresponding response functions as well as the internal energy are calculated and examined in detail in order to feature the real nature of phase boundaries and corresponding temperatures. The thermal variations of the average magnetization are classified according to the Néel nomenclature. Дослiджено магнiтнi властивостi змiшаної спiн-1/2 та спiн-7/2 моделi Iзiнга з кристалiчним полем у поздовжньому магнiтному полi на ґратцi Браве з використанням точних рекурсивних спiввiдношень. Побудована фазова дiаграма основного стану. Температурно-залежна фазова дiаграма продемонстрована для випадку однорiдного кристалiчного поля на площинi (kBT/|J|, D/|J|) при вiдсутностi зовнiшнього обмеження для координацiйних чисел z = 3, 4, 6. Параметр порядку, вiдповiдна функцiя вiдгуку i внутрiшня енергiя обчисленi та вивченi детально для встановлення справжньої природи фазових меж i вiдповiдних температур. Термiчнi змiни середньої намагнiченостi прокласифiковано вiдповiдно до номенклатури Нееля.